1999
DOI: 10.1080/136828299247432
|View full text |Cite
|
Sign up to set email alerts
|

Phonological Awareness Skills Of 4‐Year‐Old British Children: An Assessment And Developmental Data

Abstract: This study reports developmental data for the phonological awareness and processing skills of 57 normally developing Tyneside preschool children, aged between 46 and 58 months. The children were assessed on eight tasks: consistency of word production, phonological variability according to speech production task, non-word imitation, syllable segmentation, rhyme awareness, alliteration awareness, phoneme isolation and phoneme segmentation. The results indicated that girls and boys performed similarly; socio-econ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(8 citation statements)
references
References 47 publications
1
5
1
1
Order By: Relevance
“…These findings are not in agreement with the study of Burt et al [38], which reports an outstanding advantage of higher SES on several phonological awareness measures. There is evidence that students who belong to groups that rank lower on SES scales present lower levels of phonemic awareness development as a consequence of poor early language stimulation [28].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These findings are not in agreement with the study of Burt et al [38], which reports an outstanding advantage of higher SES on several phonological awareness measures. There is evidence that students who belong to groups that rank lower on SES scales present lower levels of phonemic awareness development as a consequence of poor early language stimulation [28].…”
Section: Discussioncontrasting
confidence: 99%
“…These results are in line with the study by Seixas [9], in which no gender differences were observed in morphological awareness tasks. Our results also support the study of Burt et al [38] who showed that males and females scored equivalently on phonological awareness measures. However, it should be highlighted that in the present study, the scores used represent a combination of several types of metalinguistic abilities.…”
Section: Discussionsupporting
confidence: 92%
“…This developmental progression could be confirmed for German-speaking children [e.g., [4,5]]. There is consensus that preschool children can already successfully complete syllable- and onset-rhyme tasks [3,6]. However, it is still debated whether phoneme awareness can be acquired in the absence of formal literacy instruction [7,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Word onset identification tasks are chosen frequently to assess children's phoneme awareness [e.g., [2,3,6,11,12]]. When designing such a task, it is important to control onset complexity and to differentiate between different linguistic units (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Μασούρα κ. α., 2004· Gathercole & Baddeley, 1989, του κοινωνικο-̟ολιτισµικού ̟λαισίου εντός του ο̟οίου µεγαλώνουν (̟.χ. Campbell, Dollaghan, Needleman, & Janosky, 1997· Oetting & Cleveland, 2006 και του κοινωνικο-οικονοµικού ε̟ι̟έδου των οικογενειών (Burt, Holm, & Dodd, 1999;Dollaghan & Campbell, 1998· Ellis Weismer et al, 2000· Engel, Santos, & Gathercole, 2008)· η χορήγησή της είναι ̟ρακτικά εύκολη, σύντοµη και οικονοµική, ενώ ̟αράλληλα, ό̟ως ̟ροαναφέρθηκε, οι ε̟ιδόσεις σε αυτή α̟οτελούν έναν σηµαντικό κλινικό δείκτη γλωσσικών διαταραχών (̟.χ. Bishop et al, 1996).…”
Section: η χορήγηση της δοκιµασίας ε̟ανάληψης ψευδολέξεων σε ̟αιδιά µunclassified